Patient satisfaction in ambulatory anesthesia assessed by the Heidelberg Peri-anaesthetic Questionnaire: a cross-sectional study - Lemos, Jeconias Neiva [UNESP]; Lemos, Lavínia Dantas Cardoso Neiva; Solla, Davi Jorge Fontoura; Lemos, Danilo Dantas Cardoso Neiva; Módolo, Norma Sueli Pinheiro [UNESP] (Elsevier, 2022)
Background: Service quality in anesthesiology has been frequently measured by morbidity and mortality. This measure increasingly considers patient satisfaction, which is the result of care from the client's perspective. Therefore, anesthesiologists must be able to build relationships with patients, provide understandable information and involve them in decisions about their anesthesia. This study aimed to evaluate the peri-anesthetic care provided by the anesthesia service in an ambulatory surgery unit using the Heidelberg Peri-anaesthetic Questionnaire. Methods: This cross-sectional study used the Heidelberg Peri-anaesthetic Questionnaire to evaluate 1211 patients undergoing ambulatory surgery. We selected questions that showed a greater degree of dissatisfaction and correlated them with patient characterization data (age, sex, education, and ASA physical status), anesthesia data (type, time, and prior experience), and surgical specialty. Results: Questions in which patients tended to show dissatisfaction involved fear of anesthesia and surgery, feeling cold, the urgent need to urinate, pain at the surgical site, and the team's level of concern and speed of response in relieving the patient's pain. Conclusion: The Heidelberg Peri-anaesthetic Questionnaire proved to be a useful tool in identifying points of dissatisfaction, mainly fear of anesthesia and surgery, feeling cold, the urgent need to urinate, pain at the surgical site, and the team's level of concern and speed of response in relieving the patient's pain in the population studied. These were correlated with patient, anesthesia, and surgical variables. This allows the establishment of priorities at the different points of care, with the ultimate goal of improving patient satisfaction regarding anesthesia care.
Keywords: Ambulatory surgical procedures; Patient satisfaction; Perioperative care; Professional-patient relations; Quality management; Surveys and questionnaires